Adverse events as transitional markers - Using liminality to understand experiences of second victims. (January 2021) - Schrøder, Katja; Janssens, Astrid; Hvidt, Elisabeth Assing
Abstract: Healthcare professionals are socialized into a tacit, professional identity of competences and skills – to save lives, repair trauma and facilitate good and trustful relational care. When severe adverse events happen, healthcare professionals may struggle to accept their own fallibility, and the event may pose a threat to the selfdeclared 'superior' or 'infallible' professional identity. The consequences of a sudden identity shift between the 'potentially infallible HCP' and 'potentially fallible HC P' caused by an adverse event is the analytical object of this study. The aim of the paper is to derive new understandings of how HCPs in maternity services experience adverse events by using Arnold van Gennep's and Victor Turner's 'rites of passage' theorizations and the concept of liminality to explain the process of transition between the two professional identities. Through five focus groups conducted in June 2018 with midwives and obstetricians-gynecologists, we have examined i) how second victim experiences can be understood using theories of transition and liminality, and ii) how the organizational procedures in a Danish university hospital may serve as a ritual for the involved HCPs in the aftermath of adverse events. The findings suggest that the inconsistency in the level of support contributes to the chaos that may be experienced by the healthcare professional. The organizational structure does not provide rites of transition or any other ritual processes, except for debriefings that, in many cases, are experienced as deficient. Since liminal states suggest danger and threat, because the previous professional identity is replaced by ambiguity and separation, the lack of clear rituals and support may put further strain on the HCP adding to the associated psychological and social distress. Considering the liminality and the need for structured transition rites within the work environment may prove useful when constructing adequate second victim support programs. Highlights: Healthcare professionals involved in adverse events are described as second victims. Severe adverse events may cause a sudden identity shift for healthcare professional. Theories on liminality and rituals provide insights to this transition. Inconsistent level of support adds to the chaos experienced by second victims. Structured transition rites may prove useful for second victims.